Ngebuyan: assessing younger generations’ familiarity with Sarawak Kenyah minority ethnics’ oral tradition / Nur Farah Fadhliah … [et al.] - Fadhliah, Nur Farah; Rich Joseph, Stefanie Natasha; Jafri, Fakhira; Robert, Cindy; Jeffry, Joyslyn Andrea (Universiti Teknologi MARA, Sabah, 2024)
The notion of "oral tradition" encompasses a dynamic and diverse medium of oral-aural communication that enables the creation, preservation, and transmission of knowledge on cultural heritage and serves to uphold linguistic diversity and cultural identity. Modernisation and higher literacy rates have decreased younger generations’ awareness of indigenous oral traditions despite their integral role in heritage preservation. Thus, this study examines Bumiputera younger generations’ familiarity and understanding of minority ethnic oral traditions in Sarawak. One pivotal objective is to safeguard the diminishing Sarawak Kenyah oral tradition, notably Ngebuyan. This supports UNESCO's SDG 11 of Sustainable Cities and Communities, which includes cultural preservation. This study employs a mixed methodology, primarily descriptive qualitative analysis. The study engaged a total of 109 participants, who are undergraduate students from UiTM Sarawak Branch, Malaysia. The findings showed that a substantial proportion, approximately 86.2%, exhibited a degree of awareness concerning oral traditions in a general context. Notably, 89% demonstrated the ability to differentiate between diverse oral tradition modes. Regrettably, a mere 33% of the respondents were actively involved in practising oral traditions. This observation indicates a gradual decline in the adoption of oral tradition practices as a result of limited participation among younger generations. Therefore, this research serves as a valuable addition to the existing literature, playing a pivotal role in facilitating intergenerational mechanisms for preserving cultural traditions and ensuring their continuous transmission throughout generations to come.